2009
DOI: 10.1055/s-0029-1218006
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious Concise Synthesis of Benzo[b]pyrano[2,3-d]oxepines and Dibenzo[b,d]oxepines

Abstract: An Expeditious Concise Synthesis of Benzo[b]pyrano[2,3-d]oxepines and Dibenzo[b,d]oxepines S y n t h e s i s o f B e n z o [ b ] p y r a n o [ 2 , 3d ] o x e p i n e s a n d D i b e n z o [ b , d ] o x e p i n e s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As a result, the overall strategy gives facile access to the diverse dibenzoxepanes requiring only 2 to 3 reaction steps, which is an ideal starting point for the elucidation of structure–activity relationships. Known applications of dibenzoxepanes comprise different fields of medicinal chemistry, [22a,b,c] natural product synthesis, [22d,e] and mechanistic studies, [22f,g] whereas the reported synthetic studies further underline the general interest in this compound class [22h,i] . This is also the case for the spirocyclic compound 11 l , which constitutes the key structural element of several natural products of the kadsuralignan and interiorin type, which are known for their antioxidant and anti‐HIV properties [23]…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the overall strategy gives facile access to the diverse dibenzoxepanes requiring only 2 to 3 reaction steps, which is an ideal starting point for the elucidation of structure–activity relationships. Known applications of dibenzoxepanes comprise different fields of medicinal chemistry, [22a,b,c] natural product synthesis, [22d,e] and mechanistic studies, [22f,g] whereas the reported synthetic studies further underline the general interest in this compound class [22h,i] . This is also the case for the spirocyclic compound 11 l , which constitutes the key structural element of several natural products of the kadsuralignan and interiorin type, which are known for their antioxidant and anti‐HIV properties [23]…”
Section: Methodsmentioning
confidence: 99%
“…For general background to the synthesis and properties of the title compound, see: Suau et al (1996); Tandon et al (2009). For the biological activity of methoxydibenzooxepin-one derivatives, see: Yoshioka et al (1978).…”
Section: Related Literaturementioning
confidence: 99%
“…The methoxydibenzooxepin-one derivatives have important antiviral activity and cause attention to new synthetic methods and investigation of similar compounds (Yoshioka et al, 1978). Many methoxydibenzooxepin-one derivatives directly prepared from methoxy 2-(biphenyl-2-yloxy) acetyl chloride (Suau et al, 1996;Tandon et al, 2009). The 2,9,10-trimethoxydibenzo [b,d]oxepin-7(6H)-one, (Fig.…”
Section: S1 Commentmentioning
confidence: 99%
“…Results showed that in these reactions, the yield of product 8 was not uniform. We further explored the reaction of estrone (6) with tricyclic lactones (10) under the above reaction conditions which yielded tricyclic helical ring extended estrone analogues (12) instead of anticipated product (11) as shown in Scheme 2. 55 The unique photophysical, chemical and electronic properties of helical molecules 13 inspired us to examine the synthetic utility of this estrone ring transformation protocol for the synthesis of 5 helical steroids, which are hither to unreported.…”
mentioning
confidence: 99%